Symbolic values, value formation and interpersonal relations - Giacomo Corneo (Institute for the Study of Labor (IZA), 2009)
Interpersonal relations are shaped by the judgements associated with the social categories that individuals perceive in their social contacts. I develop a model of how those judgments form based on a theory of symbolic values. The model depicts the interaction between two values, one associated with an inherited ethnic trait (nationality) and one with an endogenous achievement trait (income). Individuals who are less likely to achieve are predicted to invest more value on nationalism and to have hostile relations with immigrants. Multiple equilibria are possible and better schooling may eliminate equilibria with xenophobia. Econometric findings from three large surveys corroborate the predictions derived from the theoretical model.
urn:nbn:de:101:1-20090825548
Keywords: Z1; 300; Nationalism; immigration; interpersonal relations; value systems; Ethnische Diskriminierung; Soziale Beziehungen; Soziale Werte; Bildungsniveau; Migranten; Jugendliche; Nationalismus; Deutschland